Prospective study of sport dropout: A motivational analysis as a function of age and gender - Guzman, J. F.; Kingston, K. (European Journal of Sport Science, 2012)
Introduction: This paper aimed to analyse the predictive ability of a self-determination theory (SDT) based model describing competitive sport dropout, and variance as a function of age and gender. Variables included in the model were: psychological need satisfaction, self-determined motivation, perceived conflict between sport and study, intention to practise sport, and dropout. Methods: A prospective study was performed over a period of 19 months. Variables considered as predictors of sport dropout were measured initially, and after 19 months persistence or dropout was assessed. The sample consisted of 857 athletes aged 11-19 (mean value 15.3; standard deviation = 1.77), 680 males and 177 females. Results: Structural equation modelling illustrated support for an "alternative" model that incorporated a direct relationship between psychological need satisfaction and intention to practise sport. Analysis of invariance showed that the model was consistent as a function of age and gender, i.e. no differences were found in regression weights. MANOVA, however, revealed some group differences with respect to the dependent variables. Specifically, in terms of engagement, although assessed at the start of the study, those athletes who persisted at 19 months demonstrated greater need satisfaction, self-determined motivation and intention to practise sport than those who dropped out. Age related differences were also identified: with increased age self-determined motivation and intention to practise sport decreased, while there were no differences in need satisfaction or perceived conflict between sport and study. There were no differences related to gender. Discussion: The results support previous studies that had used SDT to predict sport dropout, specifically those that had reported an inverse relationship between self-determined motivation and perceived conflict between activities. Further, it suggests that other variables (emotional) may play a specific role in predicting intention to continue engagement with sport. Conclusion: The major contribution of the study is in validating a motivational model predicting sport dropout which incorporates perceived conflict and the direct effect of psychological need satisfaction on the intention to practise sport. The invariance of regression weights between age and gender groups suggests that the relationships proposed in the model are universal.